Pediatric HIV Disclosure Intervention Improves Knowledge and Clinical Outcomes in HIV-Infected Children in Namibia. (1st May 2017) - Beima-Sofie, Kristin M.; Brandt, Laura; Hamunime, Ndapewa; Shepard, Mark; Uusiku, James; John-Stewart, Grace C.; O'Malley, Gabrielle
Abstract : Objectives: Using routinely collected data, we evaluated a nationally implemented intervention to assist health care workers and caregivers with HIV disclosure to children. We assessed the impact of the intervention on child's knowledge and health outcomes. Methods: Data were abstracted from national databases and patient charts for HIV-infected children aged 7–15 years attending 4 high-volume HIV clinics in Namibia. Disclosure rates, time to disclosure, and HIV knowledge in 314 children participating in the intervention were analyzed. Logistic regression was used to identify correlates of partial vs. full disclosure. Paired t -tests and McNemar tests were used to compare adherence and viral load (VL) before versus after intervention enrollment. Results: Among children who participated in the disclosure intervention, 11% knew their HIV status at enrollment and an additional 38% reached full disclosure after enrollment. The average time to full disclosure was 2.5 years (interquartile range: 1.2–3 years). Children who achieved full disclosure were more likely to be older, have lower VLs, and have been enrolled in the intervention longer. Among children who reported incorrect knowledge regarding why they take their medicine, 83% showed improved knowledge after the intervention, defined as knowledge of HIV status or adopting intervention-specific language. On comparing 0–12 months before vs. 12–24 months after enrollment in the intervention, VL decreased by 0.5 log10 copies per milliliter (N = 42, P = 0.004), whereas mean adherence scores increased by 10% (N = 88, P value < 0.001). Conclusions: This HIV disclosure intervention demonstrated improved viral suppression, adherence, and HIV knowledge and should be considered for translation to other settings.